PENGARUH PERSEPSI DEEP LEARNING TERHADAP BERPIKIR KRITIS SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI SMAN 1 KOTA BOGOR - Fikri Hanif; Muhamad Priyatna; Wartono Wartono (STKIP Pesisir Selatan, 2026)
This study aimed to examine the effect of students’ perceptions of the implementation of the deep learning approach on critical thinking skills in Islamic Religious Education (PAI) and Character Education at SMAN 1 Kota Bogor. A quantitative associative approach with an ex-post facto survey design was employed involving 210 tenth-grade students selected through proportionate stratified random sampling. Data were collected using a four-point Likert-scale questionnaire and analyzed through simple linear regression using SPSS 29. The results showed that students’ perceptions of deep learning (98.1%) and critical thinking skills (77.6%) were predominantly categorized as high. Regression analysis indicated a positive and significant effect of students’ perceptions of deep learning on critical thinking skills (t = 12.520; p < 0.001), with the equation Y = 4.090 + 0.793X. The R Square value of 0.430 indicated a contribution of 43.0%, while the remaining 57.0% was explained by other factors outside the model. The novelty of this study lies in examining the three dimensions of deep learning (mindful learning, meaningful learning, and joyful learning) as perceptual factors influencing critical thinking skills within the implementation of the Merdeka Curriculum in PAI and Character Education.